Plagas del arroz almacenado y sus enemigos naturales en España - Pascual Villalobos, M.J.=700 1 Carreres, R.; Riudavets, J.; Aguilar, M.; Bozal, J.M.; Garcia, M.C.; Soler, A.; Baz, A.; Del Estal, P.
(En, Es)
ilus., 18 ref.
Keywords: ARROZ; PLAGAS; CURCULIONIDAE; RHYZOPERTA DOMINICA; PLAGAS DE PRODUCTOS ALMACENADOS; ESPAÑA; GORGOJOS; SITOPHILUS ORYZAE; CRYPTOLESTES; SITOTROGA CEREALELLA; DORYPTERIS LONGIPENNIS; BLATTISOCIUS